An Islamic perspective on the rule of law - Mohd Kamal, Mohd Hisham (IIUM Press, 2022)
The rule of law means the government must operate based on the principles of law. The rule of law is significant for good governance and sustainable development. For this reason, all States need to improve this aspect in their governments. Muslim States may need motivation from the religion itself, and in order to cater to this need, this article discusses the rule of law based on the Islamic sources of reference, including verses of the Qur’ān, the practice and saying of Prophet Muḥammad (s.a.w.), and the practice of his Rightly Guided Caliphs. This article finds that the idea of the rule of law is embedded in Islam, though some of its provisions on fundamental rights may not be universally acceptable.